Educational Theory, Practice, and Policy and the Wisdom of Social Psychology. (October 2014) - Cohen, Geoffrey L.; Garcia, Julio
The power of psychologically based interventions has garnered much interest in the general public and in the social sciences, especially in social psychology. Among the lessons that such social-psychological interventions provide are two of special importance for educational practice and social policy. The first is that different students can perceive the same classroom differently and that these perceptions can lead to substantial differences in outcomes. The second is that timely and well-placed interventions, almost irrespective of their duration, can change students' perceptions of school and the classroom for the better. Randomized double-blind experiments show that such change is possible and can trigger lasting improvements in students' academic trajectories. In the context of closing achievement gaps, these insights offer practical solutions and a better understanding of motivation. This article focuses on how wise interventions and insights from social psychology can further apply to improve human affairs, both inside and outside the classroom.